Effect of Blanching and Drying Under Different Conditions on Retention of b-Carotene in Drumstick Leaves - Bhatnagar, Vibha; Mathew, S. (Asian Journal of Chemistry, 2012)
Drumstick leaves are abundant and cheap food source and contain high amount of b-carotene. The present study was undertaken to investigate the effect on b-carotene retention on blanching in plain and sulphited water and drying in different conditions i.e., in shade, solar drier and solar drier with forced convention. Results revealed that unblanched leaves took longer for drying but there was no significant difference on drying time of samples blanched in plain and sulphited water. However, there was significant difference between the different techniques used for drying. The b-carotene content of drumstick leaves was found to be highest for unblanched samples (11645 μg per 100 g) and lowest for samples blanched in plain water (8739 μg per 100 g). b-Carotene retention was maximum when dried in solar drier with forced convention (80 %) and least when dried in shade (50 %). The interaction of the blanching and drying treatments on b-carotene retention ranged between 85 to 50 percentage.